PENGARUH KEBERADAAN MAKAM DAN MITOSNYA TERHADAP KEBERTAHANAN WARGA DI DESA BEDONO - Jovano Nathanael; Agustinus Sutanto (Jurusan Arsitektur dan Perencanaan, 2023)
Bedono Village was originally a portrait of the life of a prosperous coastal community. Village life is filled with various activities that make the sea a source of livelihood. The village comprises groups of fishermen, farmers and fish traders, and small-medium industry players who process catches. The wheels of the local economy revolve around it so that residents can stay in the village to meet their needs. In 1998, it was the beginning of the change for the people of Bedono Village. Abrasion and land subsidence due to human activities consumed 2116.54 hectares of their native land. One by one, they started leaving their homeland, leaving the sea, looking for a safer place for their future. Besides the village, which has been partially submerged, a tomb stands upright and does not sink. It is the tomb of Sheikh Abdullah Mudzakir, a respected scholar who dedicated his life to spreading Islamic teachings. Those who already consider myth as